Time-restricted eating for patients with diabetes and prediabetes: A systematic review - Lin, Xiaoxiao; Guan, Yihong; Wu, Guomin; Huang, Jinyu; Wang, Shuai (Frontiers in Nutrition, 2022)
Background Several studies have explored the effect of time-restricted eating (TRE) on patients with diabetes and prediabetes. However, these studies have not been analyzed and summarized as a whole. We conducted a systematic review to summarize and analyze all studies about the efficacy and safety of TRE for patients with diabetes and prediabetes. Methods We conducted a comprehensive search of the Embase, PubMed and Cochrane databases and the time span was from inception to 1 May 2022. The Cochrane Collaboration’s Risk of Bias 2 (RoB2) and ROBINS-I tools were used to evaluate the quality of included studies. The effect of TRE on weight loss, insulin sensitivity, plasma glucose, and the safety of TRE were summarized and analyzed. Results In total, 7 studies with 326 participants including 5 articles with 217 patients with diabetes and 2 articles with 109 patients with prediabetes were included. The TRE windows were from 4 to 10 h. The percentages of females ranged from 0 to 90%. The mean age ranged from 35.2 to 67.5 years, and most of patients adhered to TRE. All studies were assessed as high quality. TRE may result in weight loss, and improvements in the insulin sensitivity and plasma glucose, with no severe AEs. Conclusion Time-restricted eating is a safe and feasible intervention, and may offer cardiovascular and metabolic benefits for patients with diabetes and prediabetes. Studies in this field, which should be viewed as important, are limited. Therefore, more high-quality studies are needed.